Human cystic and alveolar echinococcosis in the Tibet Autonomous Region (TAR), China. Issue 6 (November 2015) - Feng, X.; Qi, X.; Yang, L.; Duan, X.; Fang, B.; Gongsang, Q.; Bartholomot, B.; Vuitton, D.A.; Wen, H.; Craig, P.S.
Abstract Human cystic echinococcosis (CE) is known to be endemic in the Tibet Autonomous Region (TAR), China; however, there is relatively little data from hospital records or community prevalence studies, and the situation regarding occurrence of human alveolar echinococcosis (AE) is unclear. Here we review the available reports about human echinococcosis in the seven prefectures of TAR. In addition, two pilot studies by mass screening using ultrasound (with serology) were undertaken (2006/7) in Dangxiong County of Lhasa Prefecture (north central TAR) and Dingqing County of Changdu Prefecture (eastern TAR). In Dangxiong County a prevalence of 9.9% (55/557) for human CE was obtained but no human AE cases were detected. By contrast, in Dingqing County (N= 232 persons screened), 11 CE cases (4.7%) and 12 AE cases (5.2%) (including one mixed CE and AE case) were diagnosed by ultrasound. Hospital records and published reports indicated that CE cases were recorded in all of seven prefectures in Tibet Autonomous Region, and AE cases in four prefectures. Incidence rates of human CE were estimated to range from 1.9 to 155 per 100, 000 across the seven prefectures of TAR, with a regional incidence of 45.1 per 100, 000. Incidence of AE was estimated to be between 0.6 and 2.8 cases per 100, 000. Overall for TAR, human AE prevalence appeared relatively low; however, the pilot mass screening in Dingqing in eastern TAR indicated that human AE disease is a potential public health problem, possibly similar to that already well described in Tibetan communities bordering TAR in north-west Sichuan and south-west Qinghai provinces.